PERENCANAAN JARINGAN IRIGASI D.I TANJUANG BALIK KECAMATAN SUNGAI PUA KABUPATEN AGAM - Iqbal Iqbal; Surya Eka Priana; Selpa Dewi (Ensiklopedia Research and Community Service Review, 2023)
The Tanjuang Balik Irrigation Area irrigates an area of 110 hectares of rice fields. The water source for the Tanjuang Balik Irrigation Area comes from Dam Ampuah River which irrigates from Ampuah to Koto Panjang. The Tanjuang Balik Irrigation Area is ± 7 km from the center of Bukittinggi City. In the Irrigation Network Planning, design analysis must be carried out which includes analysis of rainfall, calculation of discharge, and channel dimensions. So that the irrigation system can be interpreted as an effort to provide optimal and efficient water supply in order to get maximum crop production results. The main objective of the Tanjuang Balik Irrigation Network Planning is to maintain food self-sufficiency, with an area of 110 hectares of rice fields, from the area of the rice fields it is expected to harvest 8 tons / ha each time harvest. By repairing the network and providing adequate water as needed. In planning the dimensions of the channel obtained through the rainfall process using the harpes method and the gumbel method. Discharge data is needed to determine the calculation of water availability at the intake building. To get a good discharge calculation, it is necessary to record long-term river discharge data, this is needed to reduce the occurrence of too large calculation data storage. the calculation results the gumbel analysis of 1.028 mm and the calculation result from the HASPERT analysis of 0,04 m/dt the result of the planned discharge is 1,62 m/dt for the Tertiary channel planning in D.I Tanjuang Balik , it is planned to be able to accommodate water when the discharge is maximum.Keywords:discharge, Dimension of GUMBEL and HASPERT, and Tertiary rain fall channels.